2016
DOI: 10.1007/s13762-016-1179-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of microbiological and biochemical properties of dairy sewage sludge

Abstract: The rational utilisation of sludge as organic matter application into the soil permits enrichment in nutrients such as nitrogen and phosphorus. As dairy sewage sludge contains large amounts of organic matter and minerals, utilisation of such sludge in agriculture appears to be a noteworthy proposal. However, such waste can also be a source of toxic substances, heavy metals, inhibitors, xenobiotics and potentially pathogenic microorganisms. Therefore, it is so important to monitor its microbiological and bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
4
8
0
Order By: Relevance
“…An increase in enzymes activity may be the result of enriching the soil with an additional pool of enzymes present in sediments, as well as providing organic matter as a source of carbon and nutrients stimulating the growth of soil microorganisms [54]. The rapid decrease in Dha activity observed in our study may be the result of an intensive mineralization of sewage sludge at the beginning of the experiment and it could be associated with reduction of readily available biodegradable components, which was also noted by Fr ąc et al [55] and Marschner [56].…”
Section: Effect Of Sewage Sludge and Glyphosate Application On Soil M...supporting
confidence: 82%
See 1 more Smart Citation
“…An increase in enzymes activity may be the result of enriching the soil with an additional pool of enzymes present in sediments, as well as providing organic matter as a source of carbon and nutrients stimulating the growth of soil microorganisms [54]. The rapid decrease in Dha activity observed in our study may be the result of an intensive mineralization of sewage sludge at the beginning of the experiment and it could be associated with reduction of readily available biodegradable components, which was also noted by Fr ąc et al [55] and Marschner [56].…”
Section: Effect Of Sewage Sludge and Glyphosate Application On Soil M...supporting
confidence: 82%
“…Moreover, it was found that some restriction fragments of the same length occur in all research variants, which may indicate the resistance of some common bacteria and fungi to the changes applied. As reported in the literature, both sewage sludge and glyphosate can be a source of readily available carbon, nitrogen and phosphorus for soil microorganisms, which justifies the presence of the same bacterial and fungal tRFs in all treatments [23,55]. After analyzing the Shannon biodiversity index calculated for bacterial and fungal tRFs, it was found that the greatest changes in biodiversity occurred in the second sampling date and mainly concerned soils treated with SS and SS + GL.…”
Section: Effect Of Sewage Sludge and Glyphosate Application On Soil M...supporting
confidence: 56%
“…As it was suggested by Shrivastava and Banerjee [10], the series representing HMs content in soil with sewage sludge depended on the location of the soils, and as in our study, Cd exhibited the lowest content in soils, followed by Pb. Eid et al [23] conducted a pot experiment in which, after the application of sewage sludge (50 g/kg dose) to the soil, the descending series of metal contents were determined as Zn > Cr > Ni > Cu > Pb > Cd. In the present study, a higher content of Pb in comparison with other metals is related to the location of the research objects.…”
Section: Sewage Sludge Effect On Heavy Metals Content In Soilmentioning
confidence: 99%
“…The uptake of HMs by plants depends on soil properties, sewage sludge origin and its properties and dose, plant species, plant physiology, and chemical forms of metals [23].…”
Section: Sewage Sludge Effect On Plant Yield and Its Ability To Promote Hms Accumulationmentioning
confidence: 99%
“…In addition to this ecological and environmental/agronomic risk, with fungi being opportunistic organisms, they have potential pathogenic properties for humans and animals as well (Frąc et al, 2014). Frąc et al (2017) have found in sewage sludge the fungus Trichophyton sp., which is responsible for dermatophytose.…”
Section: Pathogenic Organismsmentioning
confidence: 99%